Contextual Leadership Strategies in Facing the Challenges of Cultural Change in Islamic Education - Purnasih, Uun; Salam , Abdus; Karim, Abdul (Eduprof : Islamic Education Journal, 2025)
The main problem is the lack of flexibility of leaders in integrating cultural change without sacrificing Islamic principles. This study aims to analyze how contextual leadership can be applied in facing the challenges of cultural change in Islamic educational institutions. The novelty of this research lies in an integrative approach that connects contextual leadership strategies with the principles of Islamic education. This research uses the type of Case Study research with interview data collection methods, observations, and literature studies of SMP Islam Ar-Rahmat Majalengka. The results of the study show that contextual leadership is effective in maintaining a balance between Islamic values and global cultural dynamics. The social implication is the creation of an adaptive Islamic education environment, inclusive, and adherence to Islamic values in the midst of changing times. The results of the study show that the COMPACT (Communication, Participation, Collaboration) strategy is the main approach in leadership in this school. Open and Islamic values-based communication strengthens transparency and trust between school leaders, teachers, students, and parents. The active participation of all education stakeholders supports deliberation-based decision-making (shura). This research emphasizes the importance of collaboration with external communities and institutions contributes to maintaining a balance between Islamic traditions and the demands of modern education